(untitled) (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2025)
Skill development brought a huge revolution in India. With the introduction of the concept of skill India, the opportunity to develop skills in an individual is at boom. The concept of Skill India and transform India focuses to acquire new age skills that are best suited to meet market demand. There is growth in employment with the implementation of skills in an individual. In this research paper we explore the categories of skill development programs available to students and understand the perceptions and expectations of students who have enrolled onto a skill development program and determine their level of satisfaction with such programs. A structured questionnaire was designed and data was collected from participants (students) and Administrator (teacher). The data was analysed and interpreted by applying descriptive statistics. The study will help students in deciding whether after acquiring skills of students are able to get jobs. This study aimed to investigate the relationship between skill development opportunities and students’ employability, shedding light on the factors that bridge the gap between academic learning and practical job requirements.